Organic Phosphorus Compounds as Inhibitors of Corrosion of Carbon Steel in Circulating Cooling Water: Weight Loss Method and Thermodynamic and Quantum Chemical Studies. (2nd December 2018) - Liu, Liang; Cao, Ting-Ting; Zhang, Qi-Wei; Cui, Chong-Wei
Abstract : Circulating cooling water plays an important role in industrial water use. In this study, the corrosion inhibition effects of PBTCA, HEDP, and ATMP organic phosphorus inhibitors were investigated using the weight loss method by varying the dosage of inhibitors, ClO2 concentrations, and pH values on carbon steel in recirculating cooling water with a low concentration of ClO2 solution. The results showed that the three corrosion inhibitors had a satisfactory corrosion inhibition effect and that corrosion inhibition efficiency is positively correlated with the concentration of organic phosphorus inhibitors and pH. The average corrosion inhibition efficiency of the three inhibitors was about 80% at the concentration of inhibitors = 35 mg/L, pH = 9.0, and the concentration of ClO2 = 7.0 mg/L, of which the single-phosphorus molecular corrosion inhibitor proved to be the best inhibitor. When the ClO2 concentration was 7 mg/L, the corrosion inhibition efficiencies of the three corrosion inhibitors were relatively stable. Using the density functional theory (DFT) algorithm in the Gaussian 09 program, the optimization calculation was completed by the B3LYP/6-31G (d, p) method at the microlevel. The molecular structures of the three organic phosphorus inhibitors and the number of phosphorus-containing atoms were compared to the sustained-release properties. Organic phosphorus inhibitors, as an electronic buffer, not only provided electrons but also received electrons. They formed a complex with iron and zinc ions in water in order to attach to the surface of the carbon steel and to alleviate corrosion. In addition, the adsorption with a metal surface followed the Langmuir adsorption isotherm.